The 28 heretical theses of Meister Eckhart: (Introduction, bilingual version and apostille) - Cascante , Luis Diego (2025)
This paper consists of two parts. The first part is the translation from the Latin of Meister Eckhart’s 28 heretical theses. The second part, an apostille to the 28 heretical theses.